The anticancer drug ellipticine is a potent inducer of rat cytochromes P450 1A1 and 1A2, thereby modulating its own metabolism - Aimová, Dagmar; Svobodová, Lucie; Kotrbová, Vera; Mrázová, Barbora; Hodek, Petr; Hudecek, Jirí; Václavíková, Radka; Frei, Eva; Stiborová, Marie (Drug metabolism and disposition: the biological fate of chemicals, 2007)
Ellipticine is an antineoplastic agent whose mode of action is based mainly on DNA intercalation, inhibition of topoisomerase II, and formation of covalent DNA adducts mediated by cytochromes P450 (P450s) and peroxidases. Here, this drug was found to induce CYP1A1 and/or 1A2 enzymes and their enzymatic activities in livers, lungs, and kidneys of rats treated (i.p.) with ellipticine. The induction is transient. In the absence of repeated administration of ellipticine, the levels and activities of the induced CYP1A decreased almost to the basal level 2 weeks after treatment. The ellipticine-mediated CYP1A induction increases the DNA adduct formation by the compound. When microsomal fractions from livers, kidneys, and lungs of rats treated with ellipticine were incubated with ellipticine, DNA adduct formation, measured by (32)P-postlabeling analysis, was up to 3.8-fold higher in incubations with microsomes from pretreated rats than with controls. The observed stimulation of DNA adduct formation by ellipticine was attributed to induction of CYP1A1 and/or 1A2-mediated increase in ellipticine oxidative activation to 13-hydroxy- and 12-hydroxyellipticine, the metabolites generating two major DNA adducts in human and rat livers. In addition to these metabolites, increased formation of the excretion products 9-hydroxy- and 7-hydroxyellipticine was also observed in microsomes of rats treated with ellipticine. Taken together, these results demonstrate for the first time that by inducing CYP1A1/2, ellipticine increases its own metabolism, leading both to an activation of this drug to reactive species-forming DNA adducts and to detoxication metabolites, thereby modulating to some extent its pharmacological and/or genotoxic potential.
Keywords: Liver; messenger RNA; Rats; játra; Male; mikrozomy; enzymová indukce; DNA Adducts; Rats, Wistar; mužské pohlaví; cytochrom P-450 CYP1A1; Antineoplastic Agents; Microsomes; krysa rodu Rattus; Ellipticines; Enzyme Induction; cytochrom P-450 CYP1A2; ženské pohlaví; Cytochromes; protinádorové látky; zvířata; plíce; elipticiny; Cytochrome P-450 CYP1A2; RNA, Messenger; ledviny; potkani Wistar; Kidney; Female; adukty DNA; Lung; cytochromy; Cytochrome P-450 CYP1A1; Animals